2011
DOI: 10.1038/emboj.2011.100
|View full text |Cite
|
Sign up to set email alerts
|

The oligomeric state of CtBP determines its role as a transcriptional co-activator and co-repressor of Wingless targets

Abstract: C‐terminal‐binding protein (CtBP) is a well‐characterized transcriptional co‐repressor that requires homo‐dimerization for its activity. CtBP can both repress and activate Wingless nuclear targets in Drosophila. Here, we examine the role of CtBP dimerization in these opposing processes. CtBP mutants that cannot dimerize are able to promote Wingless signalling, but are defective in repressing Wingless targets. To further test the role of dimerization in repression, the positions of basic and acidic residues tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
63
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 72 publications
3
63
1
Order By: Relevance
“…We previously observed that a soluble CtBP1(A52D) may act as a dominant negative mutant in a cellular model of p21 expression (21), further suggesting that CtBP1 can interact with its binding partners when not bound to chromatin. Interestingly, the possibility of a functional monomeric CtBP pool has been proposed (18,30). Taken together, these results suggest that the activities of CtBP1 are not exclusively downstream of NAD ϩ binding and that CtBP1 can interact with its targets without dimerizing, potentially having a regulatory role as a monomer or dimer.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…We previously observed that a soluble CtBP1(A52D) may act as a dominant negative mutant in a cellular model of p21 expression (21), further suggesting that CtBP1 can interact with its binding partners when not bound to chromatin. Interestingly, the possibility of a functional monomeric CtBP pool has been proposed (18,30). Taken together, these results suggest that the activities of CtBP1 are not exclusively downstream of NAD ϩ binding and that CtBP1 can interact with its targets without dimerizing, potentially having a regulatory role as a monomer or dimer.…”
Section: Discussionmentioning
confidence: 60%
“…6) clearly show intra-nuclear self-association, but how CtBP1 maintains a pool of monomers or if CtBP1 is immediately directed to associate by NAD(H) or responds to varying intra-nuclear dinucleotide concentrations (7,14) has not been definitively described using a cellular model of gene expression. CtBP1 monomers may have important biologic activities as recently shown in Drosophila for Wingless targets (18) and the ability of CtBP1 to recruit chromatin-modifying enzymes as a monomer may have important regulatory functions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations